Influência da penetração de instrumentos, empregados na condensação lateral ativa, na qualidade da obturação de canais radiculares - Pinheiro, Bethânia Camargo; Bramante, Alexandre Silva; Hussne, Renata Pardini [UNESP] (Faculdade De Odontologia De Bauru - USP, 2003)
PURPOSE: the purpose of this study was to compare the quality of the obturation and the difference of penetration depth inside the root canal of the instruments Finger Spreader, file type Kerr, Flexofile and Nitiflex when used as spreaders during the filling by Active Lateral Condensation Technique. MATERIAL AND METHOD: 40 extracted permanent human teeth were instrumented by the Modified Goerig Technique and divided in four groups. In the group I the finger spreader was used; in the group II, files type Kerr was used; in the group III, files Flexofile was used and, in the group IV, files Nitiflex, all number 30, for space opening for placement of the secondary cones, during the Technique of Active Lateral Condensation. The radiographic quality of the obturation and the depth of penetration of the instruments was evaluated and analysed statisticaly (Kruskal-Wallis and Dunn's Test). RESULTS AND CONCLUSION: with relationship to the radiograph analysis of the quality of the filling, the group II was what it presented the best result, followed by the groups I, IV and III, respectively. In relation to the depth of penetration of the instruments, the group IV approached more the desired distance, or, 1 millimeter less than the length of the work, followed, respectively, by groups II, III and I.

OBJETIVO: comparar a qualidade da obturação e a diferença de profundidade de penetração, no interior do canal radicular, dos espaçadores digitais (Finger Spreader), limas tipo Kerr, Flexofile e Nitiflex, quando utilizados como espaçadores, durante a obturação pela Técnica da Condensação Lateral Ativa. MATERIAL E MÉTODOS: foram utilizados 40 dentes molares permanentes humanos, extraídos, instrumentados pela Técnica de Goerig Modificada e divididos em quatro grupos. No grupo I foi utilizado o espaçador digital C; no grupo II, lima tipo Kerr; no grupo III, lima Flexofile e, no grupo IV, lima Nitiflex, todos com diâmetro (D1) ou diâmetro da ponta correspondente ao diâmetro de uma lima 30 (0,30mm), para abertura de espaço para colocação dos cones secundários, durante a Técnica da Condensação Lateral Ativa. Avaliou-se e submeteu-se à análise estatística (Kruskal-Wallis e teste de Dunn) a qualidade radiográfica da obturação e a profundidade de penetração dos instrumentos. RESULTADOS E CONCLUSÃO: quanto à análise radiográfica da qualidade da obturação, o grupo II foi o que apresentou o melhor resultado, seguido dos grupos I, IV e III, respectivamente. Em relação à profundidade de penetração dos instrumentos, o grupo IV aproximou-se mais da distância desejada, ou seja, 1 milímetro aquém do comprimento de trabalho, seguido, respectivamente, dos grupos II, III e I.
Influence of the penetration of instruments, used in the active lateral condensation, in the quality of root canal filling
Keywords: Root canal obturation; Dental instruments; Finger spreader; Obturação do canal radicular; Instrumentos odontológicos; Espaçadores